Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.3171/jns.1998.88.4.0634
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral artery injury in C1–2 transarticular screw fixation: results of a survey of the AANS/CNS Section on Disorders of the Spine and Peripheral Nerves

Abstract: Including both known and suspected cases, the risk of VA injury was 4.1% per patient or 2.2% per screw inserted. The risk of neurological deficit from VA injury was 0.2% per patient or 0.1% per screw, and the mortality rate was 0.1%. The choice of management of intraoperative VA injuries was evenly divided between placing the patient under observation and initiating immediate postoperative angiography with possible balloon occlusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
149
1
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 433 publications
(153 citation statements)
references
References 32 publications
(33 reference statements)
1
149
1
2
Order By: Relevance
“…Placement of either C1-C2 transarticular or C2 pedicle screws has a potential risk of vertebral artery injury [1][2][3][4][5][6][7][8][9][10][11][12][13][14]21]. The risk of vertebral artery injury by these two techniques needs to be carefully analyzed so as to allow the surgeon to choose the appropriate screw insertion method.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Placement of either C1-C2 transarticular or C2 pedicle screws has a potential risk of vertebral artery injury [1][2][3][4][5][6][7][8][9][10][11][12][13][14]21]. The risk of vertebral artery injury by these two techniques needs to be carefully analyzed so as to allow the surgeon to choose the appropriate screw insertion method.…”
Section: Discussionmentioning
confidence: 99%
“…Posterior C1-C2 transarticular screw fixation can result in vertebral artery injury, with potentially catastrophic results such as vertebrobasilar insufficiency, brain stem and posterior fossa infarct, and even death [1][2][3]. The rate of vertebral artery injury has been reported to be as high as 8.2% [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Jones et al [10] reported that cervical pedicle screws have a significantly higher resistance to pull-out forces than lateral mass screws. However, due to severe spinal deformity and small anatomical size of the vertebra including the lateral mass and pedicle in most of the RA cervical lesions, these screw fixation procedures are technically demanding and pose the potential risk of neurovascular injuries [7,16,27]. Frameless stereotactic technology was first designed for intra-cranial surgery for guidance of unseen lesions [8].…”
Section: Introductionmentioning
confidence: 99%